Supporting and Inhibiting Factors for Islamic Higher Education in Strengthening Religious Moderation - Apdolah, Habib Akbar Al; Rahman, Mohammad Taufiq; Qomaruzzaman, Bambang (Jurnal Iman dan Spiritualitas, 2024)
Indonesia is facing a serious problem related to religious radicalism. Universities, which should be responsible for the education of the younger generation, are actually places that are influenced by radicalism. So that Islamic Universities, especially the State Islamic University of Sunan Gunung Djati Bandung and the Islamic University of Nusantara, have a responsibility to promote religious moderation. However, on the other hand, this university faces obstacles in implementing religious moderation. This research aims to explain and answer factors supporting and inhibiting the strengthening of religious moderation. Researchers used descriptive analytical-qualitative methods with observations and interviews. As a result, these two institutions received support from university leaders. The House of Moderation Various UIN Bandung faces obstacles related to policies that conflict with university regulations, such as statutes and regulations. The Nusantara Islamic University's Religious Moderation and State Defense Group faces problems with many students from non-Islamic boarding school backgrounds. So, language that is easy to understand is needed to convey the concept of moderation, and there are also limited funds for implementing the religious moderation program at Nusantara Islamic University.